Net Photosynthesis in Leafy Nodal Cuttings of Eucalyptus Hybrid under Intermittent Mist as Influenced by Auxin Application - Bakshi, Meena; Husen, Azamal (Indian Forester, 2002)
Net photosynthesis was monitored in coppiced shoot leafy nodal cuttings of Eucalyptus hybrid at different periods during adventitious root formation. The cuttings were treated with IBA 2000, 4000 ppm or with talcum powder (Control) and kept under intermittent mist. Significant differences in current photosynthesis of treated and untreated control cuttings were observed throughout the rooting period. IBA treated cuttings responded better in terms of photosynthetic efficiency as compared to untreated control cuttings. We concluded that current photosynthesis in Eucalyptus hybrid cuttings definitely has some role in rooting that is masked by auxin application.